Distributed cognition applied to the empirical analysis of computer supported collaborative kowledge management interactions - Rearte, Carmen (2014)
In the field of Human Computer Interaction, and more specifically in the field of Computer Supported Collaborative Work and Knowledge Management, cognitive and sociological dimensions cannot be neglected in the design of value analysis. The material and social environment models almost all cognitive processes because the vast majority of them are mediated by the interaction with other agents and other artifacts. Computers connected to the Internet, are becoming fundamental elements of these interactions. Following these premises, in this paper, a methodological framework is applied, called MAIA (Methodology for the analysis of the interaction between agents of a socio-technical system), structured and based on distributed cognition in order to facilitate the analysis of a collaborative Web system oriented to knowledge management in an academic context, at high university level. Specifically, the analysis focuses on the interactions of cognitive agents that occur during the cycle of knowledge management (activities to use, create, distribute and share knowledge), and on how they affect coordination, communication and collaboration, key aspects of group work.